2011
DOI: 10.2478/v10045-011-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

Plant Extract Effect on Seed-Borne Pathogenic Fungi from Seeds of Paddy Grown in Southern India

Abstract: A total of 40 seed samples of different cultivars of paddy, collected from southern part of India, were mycologicaly analyzed by agar plating method on Czapek's-Dox-Agar (CzA) medium and Standard Blotter Method (SBM), revealed the occurrence of 33 diverse fungal species belonging to 16 genera. The species of Drechslera oryzae (RP 82.5%) was recorded with the incidence and relative preponderance (RP), followed by Curvularia lunata (RP 67.5%) and Aspergillus niger (RP 65.0%) respectively. The data on the diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 19 publications
(21 reference statements)
2
30
0
1
Order By: Relevance
“…On the other hand, D. stramonium exhibited 58.23% and 49.36% mycelium growth inhibition against F. moniliforme and C. lunata, respectively after 7 days of incubation. Our results supported by earlier works (Mohana et al, 2011) who found that, botanical extract of L. inermis was able to inhibit mycelial growth of C. lunata and F. moniliforme as 64.6% and 81.4%, respectively. It has been found that the botanical extract of L. inermis interfere with the metabolic activity of the fungi and inhibit the production of catalase in F. oxysporum (Khan & Nasreen, 2010).…”
Section: Germination Rate and Determination Of Vigor Indexsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, D. stramonium exhibited 58.23% and 49.36% mycelium growth inhibition against F. moniliforme and C. lunata, respectively after 7 days of incubation. Our results supported by earlier works (Mohana et al, 2011) who found that, botanical extract of L. inermis was able to inhibit mycelial growth of C. lunata and F. moniliforme as 64.6% and 81.4%, respectively. It has been found that the botanical extract of L. inermis interfere with the metabolic activity of the fungi and inhibit the production of catalase in F. oxysporum (Khan & Nasreen, 2010).…”
Section: Germination Rate and Determination Of Vigor Indexsupporting
confidence: 92%
“…Among the three concentrations of Bavistin, the lower dose (0.5 gm/l) showed the maximum (65.08%) inhibition of mycelium growth of F. moniliforme, after 7 days of incubation. Similarly, earlirer worker also found that Bavistin perform better mycelial growht inhibition of F. moniliforme (Mohana et al, 2011), F. oxysporum (Mamun et al, 2016;Rajput et al, 2006) and F. solani (Maitlo et al, 2015). In case of C. lunata, the maximum (50.46%) mycelium growth inhibition was reported due to 0.5 gm/l concentration of Bavistin but comparatively lower inhibition (29.05% and 27.23%) were observed due to 1.00 gm/l and 2.00 gm/l concentration, respectively after 7 days of incubation.…”
Section: Germination Rate and Determination Of Vigor Indexmentioning
confidence: 92%
See 1 more Smart Citation
“…The extract of different parts of higher plants have been reported to exhibit antifungal properties under laboratory trials (19) . Plant parts and their constituents of some higher plants have already been reported to be of successful nature of fungitoxicant because of their lesser phytotoxicity, systemicity, easily vertigratability and favourable effect for the growth of host.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty per cent inhibition of radial growth of the test fungus was recorded at 10% concentration of ethanol whereas ethanol extract of D. metel and M. indica completely inhibited the radial growth of the test fungus at the same concentration. Mohana et al (2011) reported that methanol extract of Acacia nilotica, Caesalpinia coriaria, Decalepis hamiltonii, Emblica officinalis, and Lawsonia inermis showed significant antifungal activity at 3500 μg/ml concentration on seed pathogens viz. Alternaria alternata, Aspergillus flavus, Curvularia lunata, Drechslera oryzae, D. halodes, Fusarium moniliforme, Pyricularia oryzae and Trichoconis padwickii by poisoned food technique.…”
Section: -T I =mentioning
confidence: 99%